Modelagem de um sistema multiparâmetro para monitoramento da qualidade da água utilizando internet das coisas - Leal Júnior, Wilmar Borges (Universidade Federal do Tocantins, 2020)
This work presents the development and practical application of an automation system for water quality monitoring, using the concept of internet of things - IoT. The integrated water quality monitoring system for decision support and support will be implemented and used at the Federal Institute of Tocantins, campus Dianópolis-TO, with the purpose of assisting Agrarian Sciences professionals in the automatic monitoring of water quality with application hydroponics system. This new development paradigm allows us to integrate lowcost sensors into embedded systems, thereby creating a cluster of interconnected physical objects, embedded in electronics, software, sensors, and network connectivity. This implementation aims to analyze the feasibility of developing a low cost system for monitoring water quality. In summary, the initial application will be performed in a hydroponics system, thus, the integrated monitoring and decision support system was tested, verifying the feasibility of use to support the researcher in the automatic collection and analysis of data, contributing significantly to collection and decision making.